2004
DOI: 10.1016/j.spa.2004.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of time reversal for waves in time-dependent random media

Abstract: This paper addresses the impact of time fluctuations of a random medium on refo-cusing during a time-reversal experiment. Even in the presence of moderate time-perturbations a coherent refocused pulse is observed. The theory predicts the level of recompression observed as well as the conditions for the loss of statistical stabilization. It is shown that the statistical properties of the refocused pulse depend on a simple set of parameters that describe the correlation degree of the medium. The refocused pulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, the accuracy to which we need to know the Green function is quite high. In a series of recent papers [1,12,13], it was shown that even quite small errors in the estimate of the Green function could very much perturb the refocusing properties of the time reversed signal. Sufficiently accurate knowledge of the media at the microscopic level is therefore out of reach in many interesting applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the accuracy to which we need to know the Green function is quite high. In a series of recent papers [1,12,13], it was shown that even quite small errors in the estimate of the Green function could very much perturb the refocusing properties of the time reversed signal. Sufficiently accurate knowledge of the media at the microscopic level is therefore out of reach in many interesting applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the computational cost of 3D back propagation in the model domain is much higher than the 2D case. Statistical analysis (Alfaro Vigo et al 2004) and a broader frequency bandwidth should also be considered in future studies. However, the degree of applicability of the time-reversal method at higher frequencies in outdoor environment remains a challenging question to be answered.…”
Section: Resultsmentioning
confidence: 99%
“…The ansatz (15) corresponds to a plane wave propagating along the z-axis with a slowly varying transverse envelope. In the regime ε 1, it has been shown in [12] that the forward-scattering approximation in the negative z-direction and the white-noise approximation are valid, which means that the second-order derivative in z in (16) can be neglected and the random potential 1 ε µ x, z ε 2 can be replaced by a white noise. The mathematical statement is that the functionφ ε (ω, x, z) weakly converges to the solutionφ(ω, x, z) of the Itô-Schrödinger equation 172i…”
Section: 2mentioning
confidence: 99%
“…In the time-reversal interpretation, this means that the wave backpropagates in a different realization of the random medium. We know that time-reversal refocusing is sensitive to any change in the medium [1,2], so we can anticipate that random scattering is not good for ghost imaging.…”
mentioning
confidence: 99%